2023
DOI: 10.1039/d3na00159h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in the fabrication and photocatalytic applications of graphitic carbon nitride-tungsten oxide nanocomposites

Muhammad Ikram Nabeel,
Dilshad Hussain,
Naseer Ahmad
et al.

Abstract: The present review focuses on the widely used graphitic carbon nitride (g-C3N4)-tungsten oxide (WO3) nanocomposite for photocatalytic applications. These catalysts are widely employed due to their easy preparation, high physicochemical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 156 publications
(280 reference statements)
0
5
0
Order By: Relevance
“…Therefore, highly crystalline GCNs with low surface defects have gained much interest in photocatalytic wastewater treatment in recent years. 89…”
Section: Graphitic Carbon Nitride (Gcn) As An Active Photocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, highly crystalline GCNs with low surface defects have gained much interest in photocatalytic wastewater treatment in recent years. 89…”
Section: Graphitic Carbon Nitride (Gcn) As An Active Photocatalystmentioning
confidence: 99%
“…Therefore, highly crystalline GCNs with low surface defects have gained much interest in photocatalytic wastewater treatment in recent years. 89 Chang et al copolymerized urea with 2-aminothiophene-3carbonitrile (ATCN), followed by polymerization under a salt melt (NaCl/KCl) condition to promote charge separation and light absorption capacity. 48 They found that the composition of urea and ATCN plays a crucial role in the light absorption capacity.…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…These electron-hole pairs can then participate in various chemical reactions on the MXene surface or with other environmental substances. This ability to initiate and facilitate chemical reactions under light exposure makes MXene a promising material for water purification, air purification, and energy conversion applications [38][39][40][41]. For example, removing antibiotics from water sources is a pressing environmental concern due to its implications for human health and ecosystem sustainability [42].…”
Section: Principle Of Mxene-based Photocatalysismentioning
confidence: 99%
“…Therefore, a new strategy must be designed and developed to solve this problem. 21 As the pioneer in the field of g-C 3 N 4 photocatalyst for hydrogen generation, Wang et al has continued its research and achieved a series of significant breakthroughs. 22–25 For example, the poly (triazine imide) modified with Rh/Cr 2 O 3 and CoO x cocatalysts was designed, which largely improved the charge separation efficiency and restrained the undesired backward reaction, achieving an apparent quantum efficiency of 20.2% for photocatalytic overall water splitting.…”
Section: Introductionmentioning
confidence: 99%